2016
DOI: 10.1002/lno.10311
|View full text |Cite
|
Sign up to set email alerts
|

High methane emissions from thermokarst lakes in subarctic peatlands

Abstract: The thawing and subsidence of frozen peat mounds (palsas) in permafrost landscapes results in the formation of organic‐rich thermokarst lakes. We examined the effects of palsa degradation on CH4 and CO2 emissions by comparing thermokarst lakes at two peatland locations in subarctic Québec, Canada: in the northern discontinuous permafrost region, and in southern sporadic permafrost where palsas are more rapidly degrading. The lakes were shallow (< 3 m) but stratified at both sites, and most had anoxic bottom wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(141 citation statements)
references
References 59 publications
(83 reference statements)
10
125
5
1
Order By: Relevance
“…Multiple studies have demonstrated the overall control of water column dissolved oxygen concentrations via bacterial consumption within sediments or at the water-sediment interface (Charlton 1980;del Giorgio and Williams 2005;Terzhevik et al 2010). In permafrost peatland lakes, benthic biological processes may exert a control over CO 2 production in these lakes during oxic conditions (Laurion et al 2010;Matveev et al 2016). Sedimentary oxygen uptake in SAS1B was two times higher than pelagic bacterial community demand during oxygenated summer periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated the overall control of water column dissolved oxygen concentrations via bacterial consumption within sediments or at the water-sediment interface (Charlton 1980;del Giorgio and Williams 2005;Terzhevik et al 2010). In permafrost peatland lakes, benthic biological processes may exert a control over CO 2 production in these lakes during oxic conditions (Laurion et al 2010;Matveev et al 2016). Sedimentary oxygen uptake in SAS1B was two times higher than pelagic bacterial community demand during oxygenated summer periods.…”
Section: Discussionmentioning
confidence: 99%
“…Water was collected in 2 L LDPE bottles that were filled by submerging each bottle by hand beneath the surface, emptying and refilling twice, and ensuring no air bubbles were trapped in the bottle. The dissolved gases were extracted in situ as in Matveev et al (2016): immediately after collection, 20 mL of water in the LDPE bottle was replaced by ambient air to create a headspace (100:1); the bottle was then vigorously shaken for 3 min to equilibrate the dissolved gases with the air, and then the headspace was subsampled. Ambient air samples were also taken directly in situ and stored overpressurized (10 mL of air in a 5.9 mL vial) in Labco Exetainer vials (Labco Limited, UK) sealed with butyl rubber stoppers.…”
Section: Greenhouse Gas Measurementsmentioning
confidence: 99%
“…The SAS lakes are stratified, heterotrophic lakes with anoxic zones throughout the majority of the water column, and surface waters that are under-saturated in oxygen . These lakes have abundant and active methanotrophic bacterial communities indicating their high methane supply rates (Crevecoeur et al, 2015), and they emit greenhouse gases to the atmosphere at flux rates up to 13 mmol CH 4 m −2 d −1 and 240 mmol CO 2 m −2 d −1 (Matveev et al, 2016). The valley of the Kwakwatanikapistikw River (KWK) is also in an area of sporadic permafrost, located only 8 km from SAS.…”
Section: Study Sitesmentioning
confidence: 99%
“…Notably, we used a single factor for conversion between leucine uptake to carbon production concentrations, and assumed a 2-fold isotopic dilution of leucine in the natural environment, observed in certain subarctic ecosystems (Simon and Kirchman, 1988;Simon and Azam, 1989) and as has been employed for a wide range of bacterial production studies elsewhere (Judd et al, 2006;del Giorgio et al, 1997;del Giorgio and Bouvier, 2002). However, given the wide-range of DOC concentrations and unique characteristics of thermokarst lakes, it is likely that the true conversion factors would lie on a wider range, as found in Pulido-Villena and Reche (2003).…”
Section: Controls On Bacterial Abundance and Productivitymentioning
confidence: 99%
“…These are among the most abundant freshwater ecosystems across vast areas of the circumpolar subarctic and Arctic regions (Vincent et al 2013a). These small (areas typically <10 4 m 2 ), shallow (typically <5 m) but numerous aquatic environments are known as sites of high bacterial productivity, with a correspondingly high demand for oxygen ) and as biogeochemical hotspots for greenhouse gas production (Walter Anthony et al 2014;Matveev et al 2016). Thaw ponds also contain high concentrations of photosynthetic cells, spanning a broad range of size classes (Przytulska et al 2016).…”
Section: Introductionmentioning
confidence: 99%